Association between Serum Calcium Level and Hypoxic-Ischemic Encephalopathy (HIE) Stages in Term Neonate with Perinatal Asphyxia - Jahan, Ishrat; Akter, Hazera; Hossain, Md Azizul; Najnin, Rezoana; Islam, Md Ashraful; Mannan, Kazi Abdul (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Perinatal asphyxia (PNA) is a devastating clinical condition because it causes permanent brain damage, even death of the newborn. Perinatal asphyxia is a common neonatal problem in our context. There is a need to identify neonates with PNA who will be at high risk for hypoxic ischemic encephalopathy and multi-organ dysfunction. Objective: To evaluate the association between serum calcium level and hypoxic-ischemic encephalopathy (HIE) stages in term neonate with perinatal asphyxia. Methods: A cross-sectional study was conducted in the Department of Paediatrics, Comilla Medical College Hospital, Comilla from January 2016 to July 2016. A total of 60 neonates of perinatal asphyxia with HIE of different stages were selected as cases. The gestational age was determined by regular last maternal menstrual date and New Ballard Scoring System. The perinatal asphyxia was diagnosed by using APGAR score and hypoxic ischemic encephalopathy was defined by Sarnat and Sarnat staging. Serum calcium was measured by photometric colorimetric test (OCPC method, orthocresol-phthalacin-complex) using Anatron Analyte 100 Electrolyte Analyzer. Chi-square test and ANOVA test was used to see the correlation between serum calcium and different stages of HIE. Results: Total 60 patients were included in this study, out of them 13.3 % had HIE stage I, 75% HIE stage II , 11.7% HIE stage III. Among the pt. with HIE staging in stage I, stage II and stage III had 37.5%, 71.1% and 100% of low calcium level respectively which was statistically significant. The study also showed mean ± SD serum calcium level was 9.17 ± 1.04; 8.32 ± 1.09 and 7.73 ± 0.86 in stage I, stage II and stage III respectively. There was statistically significant lower mean level of serum calcium levels observed with severity of different HIE stages (p< 0.05). Conclusion: The degree of lower serum calcium is associated with the severity of the Hypoxic Ischemic Encephalopathy (HIE) stages in neonates with perinatal asphyxia and may be used as a good, simple screening test for the early assessment of HIE stages. J Com Med Col Teachers Asso July 2024; 28(2): 87-91